Pengaruh Penerimaan Dukungan Sosial Guru Dan Self Efficacy Terhadap Student Engagement Pada Mata Pelajaran Fiqih Di Madrasah Aliyah Negeri 2 Kampar - Mastura, Nadhila; Zein, Mas’ud; Yeli, Salmaini (Peneliti.net, 2025)
This study was motivated by concerns about student engagement, as observed through various phenomena. Some students attend class but passively sit without actively participating in the learning process, while others display a lack of enthusiasm and interest, appearing bored, frequently leaving the classroom, or failing to stay focused during lessons, resulting in low engagement. This research aims to examine the influence of teacher social support and self-efficacy on student engagement in Fiqh at Madrasah Aliyah Negeri 2 Kampar. The study employs a correlational design using a quantitative approach, with multiple linear regression analysis as the data analysis technique. The population consists of all 213 students at Madrasah Aliyah Negeri 2 Kampar, and using simple random sampling with the Slovin formula, a sample of 139 students was selected. The research findings indicate that : (1) teacher social support has a positive and significant influence on student engagement in Fiqh, as shown by the partial t-test results with a t-value of 8.157 and a significance of 0.000 (< 0.05), contributing 20.1%; (2) self-efficacy has a positive and significant influence on student engagement, with a t-value of 12.040 and a significance of 0.000 (< 0.05), contributing 42.45%; and (3) teacher social support and self-efficacy together have a positive and significant simultaneous influence on student engagement, as indicated by the F-test results with an F-value of 107.754 and a significance of 0.000 (< 0.05). The combined contribution of both variables to student engagement is 61.3%, while the remaining 38.7% is influenced by other factors not examined in this study.